Pengaruh Edukasi Kesehatan Reproduksi Dengan Media Booklet Terhadap Peningkatan Pengetahuan Tentang Persiapan Masa Prakonsepsi - Nilda Yulita Siregar; Sulfa Indah Pratiwi; Lisda Widianti Longgupa; Nurfatimah Nurfatimah; Sony Bernike Magdalena Sitorus; Kadar Ramadhan (Jurnal Bidan Mandiri, 2023)
Adolescent pregnancy under the age of 20 is a problem of adolescent reproductive health which is of concern to various groups. The prevalence rate of adolescents who have had sexual intercourse in Poso Regency is 86.1% and some of them experience unwanted pregnancies. The purpose of this activity is to educate adolescents about the importance of preparing for the pre-conception period in an effort to improve the quality of future generations. The type of research used is quantitative with pre-experimental methods. The planning used is one group pre-test and post-test design. The total population in the study was 154 respondents. The number of samples is 34 respondents. The sampling technique uses Simple Random Sampling. The research instrument used a questionnaire and snakes and ladders media. Data analysis used the Wilcoxon test with a significant α<0.05. The results of the Wilcoxon test showed that the p value was 0.000 which was less than the significant value (p<0.05) indicating that reproductive health education using the snakes and ladders method increased knowledge about preconceptional preparation. Education with the snake and ladder method is very effective and must be implemented to students in increasing the preparation for the preconception period.